Roller Skating Activities as a Reflection of the Community Life Style in Semarang Municipality - Kardiyono, Kardiyono; Soegiyanto, Soegiyanto; Rahayu, Tandiyo (Universitas Negeri Semarang, 2018)
Roller skating activities have become one of the choices of urban community to develop the quality of their physical fitness. This type of sports is popular in the Municipality of Semarang and even becomes a part of sports education and sports recreation. Sports and roller skating activities conducted around Simpang Lima relate to a sports culture that identifies the lifestyle of urban communities in Semarang Municipality. The purpose of this study was to assess the activities of roller skating that became the choice of the community in Semarang Municipality, to identify community groups doing roller skating activities in the Municipality of Semarang, to describe the sports institutions that were formed, all of which became a reference for the people of Semarang Municipality, to explain the purpose of the sport skaters in conducting their activities, and to understand and explain the orientation of values that encourage the citizens to engage in the roller skating activities. The orientation of the sports values indirectly contributes to community empowerment with the high degree of community participation in sports development. It can determine the profile and progress of sports development in the region. People not only need to be encouraged to make sports as a necessity but also take a role in advancing sports achievements in the region including roller skating sports.